Kinematical analysis of two different forehand badminton drop shots techniques - Liao, W.-C.; Pan, K.-M.; Hsueh, Y.-C.; Tsai, C.-L. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to compare the kinematics variables between badminton forehand regular and reverse slice drop shots. The participants were eight elite male players. Eight Vicon Motion T20s System cameras (300Hz) were used to record the 3D kinematic data, which were computed by Visual 3D software. All the variables were tested by Wilcoxon rank analysis of variance nonparametric statistical test with the significant level at a = .05. The results showed that there was significant difference between the two forehand drop shots in the racket pan angle. The strategy of two drop shots seems different. That might because the reverse slice drop was with greater shoulder abduction movement than the regular drop shot. The players performed reverse slice drop shot might because that the abduction movement was similar with the smash.